Adult Ureteroscopy (A-URS) Checklist: A New Tool To Standardise Reporting in Endourology - Patrick Juliebø-Jones; Øyvind Ulvik; Christian Beisland; Bhaskar K. Somani (European Urology Open Science, 2023)
Ureteroscopy is increasingly being used for urolithiasis. Technological innovations have been accompanied by wide variations in practice patterns. At the same time, a common finding in many studies, especially systematic reviews, is that the heterogeneity of outcome measurements and lack of standardisation can limit both the reproducibility and generalisability of study findings. While many checklists are available to improve study reporting, there are no ureteroscopy-specific ones. The Adult-Ureteroscopy (A-URS) checklist is a practical aid for both researchers and reviewers for studies in this field. It contains five main sections (study details, preoperative, operative, postoperative, and long term data) and a total of 20 items. Patient summary: We developed a checklist to improve how studies on ureteroscopy (insertion of a telescope through the urethra to inspect the urinary tract) in adults are reported. This could help in advancing the field and improving patient outcomes, as all the key information is captured.